Enduring and Emerging Challenges of Informed Consent - Grady, Christine (The New England journal of medicine, 2015)
The author summarizes emerging standards for informed consent as the underpinning of ethical research in humans. Informed consent is a widely accepted legal, ethical, and regulatory requirement for most research and health care transactions. Nonetheless, the practice of informed consent varies by context, and the reality often falls short of the theoretical ideal. Contemporary developments in health care and clinical research call for renewed efforts to address the enduring and emerging challenges of informed consent, such as what information should be disclosed, how it should be disclosed, how much the persons providing consent should understand, and how explicit consent should be. The moral force of consent is not unique to health care or research. Integral to . . .